2014
DOI: 10.1155/2014/538053
|View full text |Cite
|
Sign up to set email alerts
|

Gender Specific Association of RAS Gene Polymorphism with Essential Hypertension: A Case-Control Study

Abstract: Renin-angiotensin system (RAS) polymorphisms have been studied as candidate risk factors for hypertension with inconsistent results, possibly due to heterogeneity among various genetic and environmental factors. A case-control association study was conducted to investigate a possible involvement of polymorphisms of three RAS genes: AGT M235T (rs699), ACE I/D (rs4340) and G2350A (rs4343), and AGTR1 A1166C (rs5186) in essential hypertensive patients. A total of 211 cases and 211 controls were recruited for this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 75 publications
(89 reference statements)
1
17
0
4
Order By: Relevance
“…Studies in south Indian also demonstrated the existence of gender-based differences in RAS gene polymorphism. 32 This difference may occur due to the regulation of RAS activity by estrogen and variations in the sensitivity of different alleles to estrogen. Clinically, the prevalence of hypertension in post-menopausal females was found to be much higher than that of pre-menopausal females; estrogen deficiency was the main reason for this difference.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in south Indian also demonstrated the existence of gender-based differences in RAS gene polymorphism. 32 This difference may occur due to the regulation of RAS activity by estrogen and variations in the sensitivity of different alleles to estrogen. Clinically, the prevalence of hypertension in post-menopausal females was found to be much higher than that of pre-menopausal females; estrogen deficiency was the main reason for this difference.…”
Section: Discussionmentioning
confidence: 99%
“…The renin-angiotensin system (RAS) is an important circulatory endocrine network that affects cardiovascular remodeling and maintains water-electrolyte homeostasis (Lis, 1999;Kumar et al, 2008). Polymorphism of RAS genes can affect the pathogenesis of hypertension and CAD, including ischemic heart disease and heart failure (Carluccio et al, 2001;Dhanachandra Singh et al, 2014). Furthermore, angiotensin is a critical component of the RAS and exerts its effects through AGTR1, which is related to vascular lesions.…”
Section: Introductionmentioning
confidence: 99%
“…The differences in allele frequency among different ethnic groups are larger, and the same between patients with hypertension and normotension . Several studies have found that among different ethnic groups, locations, and sexes, the A1166c polymorphism may play different roles for essential hypertension . It is worth noting that phenotype‐genotype relationships strongly depend on host factors such as sex, obesity, and lifestyle, in particular salt intake, as reflected by the 24‐hour urinary excretion of sodium .…”
Section: Discussionmentioning
confidence: 99%